2019
DOI: 10.1111/ecno.12141
|View full text |Cite
|
Sign up to set email alerts
|

Diaspora and government welfare spending: Do migrant remittances increase public social protection?

Abstract: This paper contributes to the debate on the impact of migrant remittances on welfare spending. It empirically examines the influence that remittances have on public social protection (SP) expenditures using macrolevel panel data on a sample of 38 high‐ and middle‐income countries over the period 2005–2014. The paper finds that remittances have a negative influence on public SP expenditures, suggesting that they serve as a private substitute to public SP. The results highlight the importance of remittances to g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 63 publications
(102 reference statements)
0
2
0
Order By: Relevance
“…They found the positive effect of public expenditure on income. Mina (2019) found the negative impact of remittance on pubic social protection expenditure. Doyle (2015) also found that remittance inflows are responsible for increasing government spending.…”
Section: Literature Reviewmentioning
confidence: 97%
“…They found the positive effect of public expenditure on income. Mina (2019) found the negative impact of remittance on pubic social protection expenditure. Doyle (2015) also found that remittance inflows are responsible for increasing government spending.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Migrant remittances to Poland have been found to reduce income inequality and poverty rates, but not as effectively as welfare transfers (Giannetti et al, 2009); while remittances can serve a social protection function, being a private measure, they tend to substitute rather than complement public provision (Mina, 2019). Privileging or relying on the market renders the realisation of social citizenship uncertain for those excluded from adequate local employment, state provision or labour mobility, whether in Poland or Ukraine.…”
Section: Citizenship Entitlement Harmsmentioning
confidence: 99%